Multi-element layered oxide material based on oxygen variable valence as well as preparation method and application of multi-element layered oxide material

By diluting the distribution of oxygen active units and manganese in the layered oxide material of sodium ion battery, the problems caused by structural phase change and oxygen valence during the charging and discharge process are solved, and the combination of high capacity and excellent cycling performance is achieved, which is suitable for sodium ion battery positive electrode materials.

CN119864410APending Publication Date: 2025-04-22CHINA INSTITUTE OF ATOMIC ENERGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411874991.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing sodium ion battery layered oxide materials are prone to irreversible structural phase change during charging and discharging, resulting in poor cyclic stability and rate performance, and the structural distortion and voltage polarization problems caused by oxygen valence are difficult to solve.

Method used

Through a small amount of multivariate doping method, multiple elements are introduced into the layered oxides, dilute the distribution of oxygen active units, reduce the over-oxidation of oxygen ions and the distribution of manganese, and reduce the structural distortion caused by manganese devalence, thereby improving the structural stability and oxygen devalence stability of the material.

Benefits of technology

It has achieved a significant improvement in the structural stability and oxygen valence stability of the material during the charging and discharging process. It not only takes advantage of the high capacity brought by oxygen valence, but also ensures excellent cycling performance. It is suitable for sodium ion battery positive electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864410A_ABST
    Figure CN119864410A_ABST
Patent Text Reader

Abstract

Mg and Mn are used as main elements, a small amount of other elements are doped, the chemical formula of the multi-element layered oxide material is NaxMMaMnbMcO2, M is multiple combinations of elements Ni, Cu, Zn, Fe, Co, Li, Al and Ti, x is larger than or equal to 0.6 and smaller than or equal to 0.72, a is larger than or equal to 0.15 and smaller than or equal to 0.33, b is larger than or equal to 0.45 and smaller than or equal to 0.8, c is larger than or equal to 0.01 and smaller than or equal to 0.31, and a + b + c is equal to 1. According to the invention, multiple elements are introduced into the layered oxide through a method of doping a small amount of multiple elements, so that on one hand, the distribution of oxygen active units can be diluted, the excessive oxidation of oxygen ions can be reduced, and on the other hand, the distribution of manganese can be reduced, and the structural distortion caused by manganese valence change can be reduced; further, the structural stability and the oxygen variable valence stability of the layered oxide in the charge-discharge process are improved, the high capacity brought by oxygen variable valence is utilized, and the excellent cycle performance is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a multi-layered oxide material based on oxygen valence change, a preparation method and use thereof. Background Art

[0002] As sodium resources are abundant, widely distributed and low in cost, sodium-ion batteries have shown great commercial potential and application value. The development of high-performance cathode materials is the key to promoting the development and application of sodium-ion batteries.

[0003] As one of the main cathode materials in the current field of sodium-ion batteries, layered oxides have the significant advantages of easy synthesis and high specific capacity. However, a large number of studies have pointed out that when the Na + When a large amount of it is released, it will cause irreversible structural phase changes. These phase changes will seriously affect the cycle stability and rate performance of the battery, limiting its application in scenarios with higher energy density requirements. The structural stability and cycle stability of layered oxides at high voltages can be improved by means of element substitution, voltage limitation, coating, etc., but a certain specific capacity will be sacrificed. Therefore, the common layered oxides based on transition metal valence change generally have a specific capacity of around 140mAh / g while ensuring excellent cycle life. How to further optimize the performance of layered oxides is an important direction in the current research of positive electrode materials for sodium-ion batteries.

[0004] Recent studies have found that oxygen in layered cathode materials for sodium-ion batteries can participate in charge compensation, providing a new valence mechanism and capacity source. This oxygen valence system can show a reversible specific capacity of more than 200 mAh / g. The oxygen valence behavior in layered oxides for sodium-ion batteries is not limited to sodium-rich materials with a Na-O-Na configuration. With the deepening of research, alkaline earth metals (AE), vacancies (□), and certain transition metals (M) can stimulate oxygen valence reactions in materials. However, after a large number of oxygen ions participate in the valence change, the stability of lattice oxygen deteriorates, and even causes structural degradation such as oxygen release and transition metal migration, which causes the material to show obvious voltage polarization, voltage decay, and capacity decay during charge and discharge. In addition, oxygen valence changes usually occur at high potentials, which also puts higher requirements on the electrolyte.

[0005] Bruce's team found that the voltage polarization of the material is related to the Li / Mn order in the transition metal layer. 0.75 Li 0.25 Mn 0.75 O 2 The P2-Na2O3 has a severe voltage polarization during the charge and discharge process. 0.6 Li 0.2 Mn 0.8O 2 The voltage polarization is very small during the charge and discharge process. Other research teams have gradually discovered that oxygen valence also exists in NiMn-based, CuMn-based, MgMn-based, and ZnMn-based layered oxides. The researchers have improved the stability of oxygen valence to a certain extent by designing a variety of structurally ordered material systems, but there are still some problems from practical application. Therefore, it is necessary to continue to find and design new positive electrode materials with excellent comprehensive electrochemical properties and oxygen redox reaction activity. Summary of the invention

[0006] The purpose of the present invention is to provide a multi-element layered oxide material based on oxygen valence change, a preparation method and a use thereof. By introducing a plurality of elements into the layered oxide through a small amount of multi-element doping method, on the one hand, the distribution of oxygen active units can be diluted to reduce the excessive oxidation of oxygen ions, and on the other hand, the distribution of manganese can be reduced, and the structural distortion caused by manganese valence change can be reduced, thereby increasing the structural stability and oxygen valence stability of the layered oxide during the charge and discharge process.

[0007] To achieve the above object, the technical solution of the present invention is as follows:

[0008] A multi-element layered oxide material based on oxygen valence, with Mg and Mn as the main elements, and a small amount of other elements doped, its chemical formula is Na x Mg a Mn b M c O 2 , M is a combination of multiple elements among Ni, Cu, Zn, Fe, Co, Li, Al, and Ti, M types ≥ 4, 0.6≤x≤0.72, 0.15≤a≤0.33, 0.45≤b≤0.8, 0.01≤c≤0.31, a+b+c=1.

[0009] Further, in a specific embodiment, the multi-layered oxide material based on oxygen valence change as described above can be:

[0010] Na 0.62 Mg 0.20 Cu 0.03 Zn 0.03 Ni 0.03 Fe 0.04 Mn 0.64 Ti 0.03 ,

[0011] Na 0.67 Mg 0.19 Cu 0.04 Zn 0.04 Ni 0.04 Fe 0.04 Mn 0.50 Ti 0.15 or

[0012] Na 0.70 Mg 0.24 Cu 0.03 Zn 0.03 Ni 0.03 Al 0.04 Mn 0.48 Ti 0.15 O 2 .

[0013] In a specific embodiment, the present invention provides a method for preparing the multi-layered oxide material based on oxygen valence change, wherein the preparation method is a solid phase method, comprising:

[0014] The required stoichiometric amounts of sodium carbonate or sodium nitrate, magnesium oxide, manganese dioxide and oxide or carbonate of M are mixed in proportion to form a precursor, wherein M is Ni 2+ , Cu 2+ 、Zn 2+ , Fe 3+ 、Co 3+ , Li + 、Al 3+ 、Ti 4+ of various kinds;

[0015] The precursors are uniformly mixed by a grinding method to obtain precursor powder;

[0016] Pre-sintering the precursor powder at 400-600° C. for 3-6 hours;

[0017] Take out the pre-sintered product, grind it thoroughly, and then sinter it at 800-1100℃ for 12-24h;

[0018] The heat-treated product is fully ground to obtain the layered oxide material.

[0019] Further, in a specific embodiment, the preparation method of the multi-layered oxide material based on oxygen valence change (solid phase method) as described above, wherein the precursor is Na 2 CO 3 or NaNO 3 、MgO、MnO 2 , and oxides or carbonates of M are mixed in a desired stoichiometric ratio according to the molar ratio of each element in the layered oxide material, wherein M is Ni 2+ , Cu 2+ 、Zn 2+ , Fe 3+ 、Co 3+ , Li + 、Al 3+ 、Ti 4+ Among them, Ni2+ , Cu 2+ 、Zn 2+ , Fe 3+ 、Co 3+ , Li + 、Al 3+ The molar percentage of Ti can be selected in the range of 0.02-0.04. 4+ The molar percentage can be selected in the range of 0.02-0.15.

[0020] Furthermore, in a specific embodiment, the preparation method of the multi-layered oxide material based on oxygen valence change (solid phase method) as described above, wherein, after obtaining the precursor powder, the precursor powder is pre-sintered in a muffle furnace at 500°C for 5 hours, taken out and fully ground, and then sintered again in a muffle furnace at 900°C for 15 hours.

[0021] In a specific embodiment, the present invention provides another method for preparing the multi-layered oxide material based on oxygen valence change, wherein the preparation method is a sol-gel method, comprising:

[0022] Sodium acetate or sodium sulfate, nitrate, acetate or sulfate containing magnesium, manganese and doping element M are dissolved in water or ethanol in a stoichiometric ratio according to the molar ratio of each element in the layered oxide material to form a precursor solution; M is specifically Ni 2+ , Cu 2+ 、Zn 2+ , Fe 3+ 、Co 3+ , Li + 、Al 3+ 、Ti 4+ of various kinds;

[0023] Stirring at 60°C-100°C, adding a proper amount of chelating agent, and evaporating to dryness to form a precursor gel;

[0024] Pre-calcining the precursor gel in an air atmosphere at 400° C. to 600° C. for 3 to 6 hours;

[0025] Then heat treat at 800℃-1100℃ for 12-24 hours;

[0026] The heat-treated product is fully ground to obtain the layered oxide material.

[0027] Further, in a specific embodiment, in the method for preparing a multi-layered oxide material based on oxygen valence change (sol-gel method) as described above, the amount of sodium acetate or sodium sulfate used is 100wt% to 108wt% of the stoichiometric amount of the required sodium.

[0028] Further, in a specific embodiment, in the method for preparing a multi-layered oxide material based on oxygen valence change (sol-gel method) as described above, the chelating agent is citric acid with a stoichiometric ratio of 100%-200% molar ratio of all salts.

[0029] The present invention further provides the use of the multi-layered oxide material based on oxygen valence change, which is used as a positive electrode material for a sodium ion battery.

[0030] In a specific embodiment, the multi-layered oxide material based on oxygen valence change is mixed with a conductive agent and a binder in proportion, uniformly coated on a current collector aluminum foil, and cut into positive electrode sheets of a sodium ion battery after drying.

[0031] Furthermore, the mass ratio of the oxygen-valence-varied multi-layered oxide material powder to the conductive agent and the binder is 8:1:1.

[0032] Furthermore, the conductive agent may be carbon nanotubes, and the binder may be PVDF.

[0033] The beneficial effects of the present invention are as follows:

[0034] 1) The present invention utilizes a small amount of multiple element doping to dilute the distribution of oxygen active units and reduce excessive oxidation of oxygen ions on the one hand, and to reduce the distribution of manganese on the other hand, thereby reducing the structural distortion caused by manganese valence change, thereby increasing the structural stability of the layered oxide during the charge and discharge process and the oxygen valence stability, thereby utilizing the high capacity brought by oxygen valence change and ensuring excellent cycle performance.

[0035] 2) Pre-sintering at 400-600°C during material preparation can make the reaction more complete and ensure the purity of the synthesized material.

[0036] 3) The layered oxide obtained by this method has both high specific capacity and excellent cycle stability, and has good application prospects in the field of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 A P2-type layered oxide material Na based on oxygen valence change prepared in the embodiment of the present invention 0.62 Mg 0.20 Cu 0.03 Zn 0.03 Ni 0.03 Fe 0.04 Mn 0.64 Ti 0.03 XRD pattern of

[0038] Figure 2 A P2-type layered oxide material Na based on oxygen valence change prepared in the embodiment of the present invention0.62 Mg 0.20 Cu 0.03 Zn 0.03 Ni 0.03 Fe 0.04 Mn 0.64 Ti 0.03 SEM photos of

[0039] Figure 3 A P2-type layered oxide material Na based on oxygen valence change prepared in the embodiment of the present invention 0.62 Mg 0.20 Cu 0.03 Zn 0.03 Ni 0.03 Fe 0.04 Mn 0.64 Ti 0.03 The charge and discharge curve at 0.1C rate;

[0040] Figure 4 A P2-type layered oxide material Na based on oxygen valence change prepared in the embodiment of the present invention 0.62 Mg 0.20 Cu 0.03 Zn 0.03 Ni 0.03 Fe 0.04 Mn 0.64 Ti 0.03 Cycling performance at 0.2C rate;

[0041] Figure 5 A P2-type layered oxide material Na based on oxygen valence change prepared in the embodiment of the present invention 0.67 Mg 0.19 Cu 0.04 Zn 0.04 Ni 0.04 Fe 0.04 Mn 0.50 Ti 0.15 XRD pattern of

[0042] Figure 6 A P2-type layered oxide material Na based on oxygen valence change prepared in the embodiment of the present invention 0.67 Mg 0.19 Cu 0.04 Zn 0.04 Ni 0.04 Fe 0.04 Mn 0.50 Ti 0.15 SEM photos of

[0043] Figure 7 A P2-type layered oxide material Na based on oxygen valence change prepared in the embodiment of the present invention 0.67Mg 0.19 Cu 0.04 Zn 0.04 Ni 0.04 Fe 0.04 Mn 0.50 Ti 0.15 The charge and discharge curve at 0.1C rate;

[0044] Figure 8 A P2-type layered oxide material Na based on oxygen valence change prepared in the embodiment of the present invention 0.67 Mg 0.19 Cu 0.04 Zn 0.04 Ni 0.04 Fe 0.04 Mn 0.50 Ti 0.15 Cycling performance at 0.2C rate;

[0045] Fig. 9 A P2-type layered oxide material Na based on oxygen valence change prepared in the embodiment of the present invention 0.70 Mg 0.24 Cu 0.03 Zn 0.03 Ni 0.03 Al 0.04 Mn 0.48 Ti 0.15 O 2 XRD pattern of

[0046] Fig.10 A P2-type layered oxide material Na based on oxygen valence change prepared in the embodiment of the present invention 0.70 Mg 0.2 4 Cu 0.03 Zn 0.03 Ni 0.03 Al 0.04 Mn 0.48 Ti 0.15 O 2 SEM photos of

[0047] Fig.11 A P2-type layered oxide material Na based on oxygen valence change prepared in the embodiment of the present invention 0.70 Mg 0.2 4 Cu 0.03 Zn 0.03 Ni 0.03 Al 0.04 Mn 0.48 Ti 0.15 O 2 The charge and discharge curve at 0.1C rate;

[0048] Fig.12 A P2-type layered oxide material Na based on oxygen valence change prepared in the embodiment of the present invention 0.70 Mg 0.2 4 Cu 0.03 Zn 0.03 Ni 0.03 Al 0.04 Mn 0.48 Ti 0.15 O 2 Cycling performance at 0.2C rate. DETAILED DESCRIPTION

[0049] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0050] Embodiment 1:

[0051] Embodiment 1 of the present invention provides a P2-type layered oxide material based on oxygen valence change, wherein the chemical formula of the P2-type material is: x Mg a Mn b M c O 2 ,

[0052] Wherein M is a combination of multiple elements among Ni, Cu, Zn, Fe, Co, Li, Al, and Ti.

[0053] The x, a, b, and c are respectively the molar percentages of the corresponding elements; 0.6≤x≤0.72, 0.15≤a≤0.33, 0.45≤b≤0.8, 0.01≤c≤0.31, and a+b+c=1.

[0054] Exemplary specific materials may be:

[0055] Na 0.62 Mg 0.20 Cu 0.03 Zn 0.03 Ni 0.03 Fe 0.04 Mn 0.64 Ti 0.03 ,

[0056] Na 0.67 Mg 0.19 Cu 0.04 Zn 0.04 Ni 0.04 Fe 0.04 Mn0.50 Ti 0.15 or

[0057] Na 0.70 Mg 0.24 Cu 0.03 Zn 0.03 Ni 0.03 Al 0.04 Mn 0.48 Ti 0.15 O 2 .

[0058] Among them, M recommends selecting at least 4 or more element combinations to achieve better material properties. Five of the above exemplary specific materials are selected, and when more element combinations are selected, the performance of the layered oxide material is basically similar.

[0059] The P2-type layered oxide based on oxygen valence change of the present invention utilizes a small amount of multiple element doping to dilute the distribution of oxygen active units and reduce excessive oxidation of oxygen ions on the one hand, and to reduce the distribution of manganese on the other hand, thereby reducing the structural distortion caused by manganese valence change, thereby increasing the structural stability and oxygen valence stability of the layered oxide during the charge and discharge process, utilizing the high capacity brought by oxygen valence change and ensuring excellent cycle performance, and having a good application prospect in the field of sodium ion batteries.

[0060] The preparation method for obtaining the material is described below.

[0061] Embodiment 2:

[0062] This embodiment provides a method for preparing a P2-type layered oxide material based on oxygen valence change, specifically a solid phase method, comprising:

[0063] The required stoichiometric amounts of sodium carbonate, magnesium oxide, manganese dioxide (or manganese carbonate) and oxide or carbonate of M are mixed into a precursor according to the molar ratio of each element in the layered oxide material in the first embodiment, wherein M is Ni 2+ , Cu 2+ 、Zn 2+ , Fe 3+ 、Co 3+ , Li + 、Al 3+ 、Ti 4+ Among them, Ni 2+ , Cu 2+ 、Zn 2+ , Fe 3+ 、Co 3 + , Li + 、Al 3+The molar percentage of Ti can be selected in the range of 0.02-0.04. 4+ The molar percentage of M can be selected in the range of 0.02-0.15; the oxide or carbonate of M can be selected such as NiO, CuO, Fe 2 O 3 , ZnO, TiO 2 , Li 2 CO 3 wait;

[0064] The precursors are uniformly mixed by a grinding method to obtain precursor powder;

[0065] The precursor powder is placed in a muffle furnace and sintered at 400-600° C. for 3-6 hours;

[0066] Take out and grind thoroughly, then sinter at 800-1100℃ for 12-24h;

[0067] The heat-treated product is fully ground to obtain the P2-type layered oxide material based on oxygen valence change.

[0068] The preparation method of the P2-type layered oxide material provided in this embodiment can be used to prepare the P2-type layered oxide material based on oxygen valence change described in the above embodiment 1. The method provided in this embodiment is simple and easy to implement, low in cost, and the materials used are safe and non-toxic, and are suitable for large-scale manufacturing applications.

[0069] Embodiment three:

[0070] This embodiment provides a method for preparing a P2-type layered oxide material based on oxygen valence change, specifically a solid phase method, comprising:

[0071] The required stoichiometric amounts of sodium nitrate, magnesium oxide, manganese dioxide (or manganese carbonate) and oxide or carbonate of M are mixed into a precursor according to the molar ratio of each element in the layered oxide material in the first embodiment, wherein M is Ni 2+ , Cu 2+ 、Zn 2+ , Fe 3+ 、Co 3+ , Li + 、Al 3+ 、Ti 4+ Among them, Ni 2+ , Cu 2+ 、Zn 2+ , Fe 3+ 、Co 3 + , Li + 、Al 3+The molar percentage of Ti can be selected in the range of 0.02-0.04. 4+ The molar percentage of M can be selected in the range of 0.02-0.15; the oxide or carbonate of M can be selected such as NiO, CuO, Fe 2 O 3 , ZnO, TiO 2 , Li 2 CO 3 wait;

[0072] The precursors are uniformly mixed by a grinding method to obtain precursor powder;

[0073] The precursor powder is placed in a muffle furnace and sintered at 400-600° C. for 3-6 hours;

[0074] Take out and grind thoroughly, then sinter at 800-1100℃ for 12-24h;

[0075] The heat-treated product is fully ground to obtain the P2-type layered oxide material based on oxygen valence change.

[0076] The preparation method of the P2-type layered oxide material provided in this embodiment can be used to prepare the P2-type layered oxide material based on oxygen valence change described in the above embodiment 1. The method provided in this embodiment is simple and easy to implement, low in cost, and the materials used are safe and non-toxic, and are suitable for large-scale manufacturing applications.

[0077] Embodiment 4:

[0078] This embodiment provides another method for preparing a P2-type layered oxide based on oxygen valence change, specifically a sol-gel method, comprising:

[0079] Sodium acetate or sodium sulfate with a stoichiometric amount of 100wt%-108wt% of the required sodium, nitrate, acetate or sulfate containing magnesium, manganese, and doping element M are dissolved in water or ethanol according to the molar ratio of each element in the layered oxide material in the above embodiment 1, and mixed into a precursor solution; M is specifically Ni 2+ , Cu 2+ 、Zn 2+ , Fe 3+ 、Co 3+ , Li + 、Al 3+ 、Ti 4+ of various kinds;

[0080] Stirring at 60° C.-100° C., adding a proper amount of a chelating agent, and evaporating to dryness to form a precursor gel; the chelating agent can be citric acid in a stoichiometric amount of 100%-200% molar ratio of all salts;

[0081] The precursor gel is placed in a crucible and pre-fired in an air atmosphere at 400° C. to 600° C. for 3 to 6 hours;

[0082] Then heat treat at 800℃-1100℃ for 12-24 hours;

[0083] The heat-treated product is fully ground to obtain the P2-type layered oxide material.

[0084] The preparation method of the P2-type layered oxide material provided in this embodiment can be used to prepare the P2-type layered oxide material based on oxygen valence change described in the above embodiment 1. The method provided in this embodiment is simple and easy to implement, low in cost, and the materials used are safe and non-toxic, and are suitable for large-scale manufacturing applications.

[0085] Embodiment five:

[0086] In this embodiment, the solid phase method described in the above embodiment 2 is used to prepare the P2 type layered oxide material based on oxygen valence change, including:

[0087] Will Na 2 CO 3 (analytical grade), NiO (analytical grade), MgO (analytical grade), CuO (analytical grade), Fe 2 O 3 (analytical pure), ZnO (analytical pure), MnO 2 (analytical grade), TiO 2 (analytical grade) according to the required stoichiometric ratio; grind in an agate mortar for half an hour to obtain a precursor; press the precursor into a tablet and transfer it to an Al 2 O 3 The crucible was treated in a muffle furnace at 500 °C for 5 hours, taken out and ground, and then pressed into a sheet and transferred to Al 2 O 3 The crucible was treated in a muffle furnace at 900 ° C for 15 hours to obtain the material Na 0.62 Mg 0.20 Cu 0.0 3 Zn 0.03 Ni 0.03 Fe 0.04 Mn 0.64 Ti 0.03 Its X-ray powder diffraction (XRD) pattern can be found at Figure 1 , from the XRD spectrum, Na 0.62 Mg 0.20 Cu 0.03 Zn 0.03 Ni 0.03 Fe 0.04 Mn 0.64 Ti0.03 The crystal structure is a P2-type layered structure. Figure 2 The scanning electron microscope (SEM) photo of this embodiment is given in FIG. 1 . It can be seen from the SEM photo that the Na 0.62 Mg 0.20 Cu 0.03 Zn 0.03 Ni 0.03 Fe 0.04 Mn 0.64 Ti 0.03 It is a bulk material.

[0088] The layered oxide material prepared above is used as the active material of the battery positive electrode material for the preparation of sodium ion batteries. The specific steps are: 0.62 Mg 0.20 Cu 0.03 Zn 0.03 Ni 0.03 Fe 0.04 Mn 0.64 Ti 0.03 The powder was fully mixed with a conductive agent (such as carbon nanotubes) and a binder (such as PVDF) in a mass ratio of 8:1:1. The slurry was evenly coated on the current collector aluminum foil in a dry environment at room temperature, dried at 120°C for 10 hours under vacuum conditions, cut into pole pieces and transferred to a glove box for standby use. The assembly of the simulated battery was carried out in an Ar atmosphere glove box, with metallic sodium as the counter electrode and NaClO 4 / ethylene carbonate:propylene carbonate=1:1, 5% fluoroethylene carbonate (EC:PC=1:1, 5% FEC) solution was used as the electrolyte and assembled into a CR2032 button cell.

[0089] Use constant current charge and discharge mode, test results see Figure 3 and Figure 4 . Figure 3 This is the charge and discharge curve of the material at a rate of 0.1C. The specific capacity of the material is 180mAh / g; Figure 4 The material has a cycling performance of 0.2C rate and a capacity retention rate of 96.5% after 50 cycles, which indicates that it has excellent comprehensive electrochemical performance.

[0090] Embodiment six:

[0091] In this embodiment, the solid phase method described in the above embodiment 2 is used to prepare the P2 type layered oxide material based on oxygen valence change, including:

[0092] Will Na 2 CO 3(analytical grade), NiO (analytical grade), ZnO (analytical grade), CuO (analytical grade), MgO (analytical grade), Fe 2 O 3 (analytical grade), MnO 2 (analytical grade), TiO 2 (analytical grade) according to the required stoichiometric ratio; grind in an agate mortar for half an hour to obtain a precursor; press the precursor into a tablet and transfer it to an Al 2 O 3 Crucible, treated at 500℃ in muffle furnace for 5 hours, taken out and ground, pressed again and transferred to Al 2 O 3 The crucible was treated in a muffle furnace at 900 ° C for 15 hours to obtain the material Na 0.67 Mg 0.19 Cu 0.04 Zn 0.04 Ni 0.04 Fe 0.04 Mn 0.50 Ti 0.15 Its X-ray powder diffraction (XRD) pattern can be found at Figure 5 , from the XRD spectrum, Na 0.67 Mg 0.19 Cu 0.04 Zn 0.04 Ni 0.04 Fe 0.04 Mn 0.50 Ti 0.15 The crystal structure is a P2-type layered structure. Figure 6 The scanning electron microscope (SEM) photo of this embodiment is given in FIG. 1 . It can be seen from the SEM photo that the Na 0.67 Mg 0.19 Cu 0.04 Zn 0.04 Ni 0.04 Fe 0.04 Mn 0.50 Ti 0.15 It is a bulk material.

[0093] The layered oxide material prepared above is used as the active material of the battery positive electrode material for the preparation of sodium ion batteries. The specific steps are: 0.67 Mg 0.19 Cu 0.04 Zn 0.04 Ni 0.04 Fe 0.04 Mn 0.50 Ti 0.15The powder was fully mixed with a conductive agent (such as carbon nanotubes) and a binder (such as PVDF) in a mass ratio of 8:1:1. The slurry was evenly coated on the current collector aluminum foil in a dry environment at room temperature, dried at 120°C for 10 hours under vacuum conditions, cut into pole pieces and transferred to a glove box for standby use. The assembly of the simulated battery was carried out in an Ar atmosphere glove box, with metallic sodium as the counter electrode and NaClO 4 / ethylene carbonate:propylene carbonate=1:1, 5% fluoroethylene carbonate (EC:PC=1:1, 5% FEC) solution was used as the electrolyte and assembled into a CR2032 button cell.

[0094] Use constant current charge and discharge mode, test results see Figure 7 and Figure 8 . Figure 7 This is the charge and discharge curve of the material at a rate of 0.1C. The specific capacity of the material is 205mAh / g; Figure 8 The material has a cycling performance of 0.2C rate and a capacity retention rate of 97% after 50 cycles, which indicates that it has excellent comprehensive electrochemical performance.

[0095] Embodiment seven:

[0096] In this embodiment, the solid phase method described in the third embodiment is used to prepare the P2-type layered oxide material based on oxygen valence change, including:

[0097] NaNO 3 (analytical pure), NiO (analytical pure), ZnO (analytical pure), CuO (analytical pure), MgO (analytical pure), Al 2 O 3 (analytical grade), MnO 2 (analytical grade), TiO 2 (analytical grade) according to the required stoichiometric ratio; grind in an agate mortar for half an hour to obtain a precursor; press the precursor into a tablet and transfer it to an Al 2 O 3 Crucible, treated at 500℃ in muffle furnace for 5 hours, taken out and ground, pressed again and transferred to Al 2 O 3 The crucible was treated in a muffle furnace at 900 ° C for 15 hours to obtain the material Na 0.70 Mg 0.24 Cu 0.03 Zn 0.03 Ni 0.03 Al 0.04 Mn 0.48 Ti 0.15 O 2 Its X-ray powder diffraction (XRD) pattern can be found at Fig. 9 , from the XRD spectrum, Na0.70 Mg 0.24 Cu 0.03 Zn 0.03 Ni 0.03 Al 0.04 Mn 0.48 Ti 0.15 O 2 The crystal structure is a P2-type layered structure. Fig.10 The scanning electron microscope (SEM) photo of this embodiment is given in FIG. 1 . It can be seen from the SEM photo that the Na 0.70 Mg 0.24 Cu 0.03 Zn 0.03 Ni 0.03 Al 0.04 Mn 0.48 Ti 0.15 O 2 It is a bulk material.

[0098] The layered oxide material prepared above is used as the active material of the battery positive electrode material for the preparation of sodium ion batteries. The specific steps are: 0.70 Mg 0.24 Cu 0.03 Zn 0.03 Ni 0.03 Al 0.04 Mn 0.48 Ti 0.15 O 2 The powder was fully mixed with a conductive agent (such as carbon nanotubes) and a binder (such as PVDF) in a mass ratio of 8:1:1. The slurry was evenly coated on the current collector aluminum foil in a dry environment at room temperature, dried at 120°C for 10 hours under vacuum conditions, cut into pole pieces and transferred to a glove box for standby use. The assembly of the simulated battery was carried out in an Ar atmosphere glove box, with metallic sodium as the counter electrode and NaClO 4 / ethylene carbonate:propylene carbonate=1:1, 5% fluoroethylene carbonate (EC:PC=1:1, 5% FEC) solution was used as the electrolyte and assembled into a CR2032 button cell.

[0099] Use constant current charge and discharge mode, test results see Fig.11 and Fig.12 . Fig.11 This is the charge and discharge curve of the material at a rate of 0.1C. The specific capacity of the material is 208mAh / g; Fig.12 The material has a cycling performance of 0.2C rate and a capacity retention rate of 96.3% after 50 cycles, which indicates that it has excellent comprehensive electrochemical performance.

[0100] The P2-type layered oxide material based on oxygen valence change provided in the embodiment of the present invention utilizes a small amount of multiple element doping to dilute the distribution of oxygen active units and reduce excessive oxidation of oxygen ions on the one hand, and to reduce the distribution of manganese on the other hand, thereby reducing the structural distortion caused by manganese valence change, thereby increasing the structural stability and oxygen valence stability of the layered oxide during the charge and discharge process, which not only utilizes the high capacity brought by oxygen valence change, but also ensures excellent cycle performance. At the same time, the preparation method is simple and has good application prospects in the field of sodium ion batteries.

[0101] Those skilled in the art will readily conceive of other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. Thus, if these variations and use adaptations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and use adaptations.

[0102] The above embodiments are merely illustrative of the present invention, and the present invention may also be implemented in other specific ways or other specific forms without departing from the gist or essential features of the present invention. Therefore, the described embodiments should be considered illustrative rather than restrictive in any respect. The scope of the present invention should be described by the appended claims, and any changes equivalent to the intent and scope of the claims should also be included within the scope of the present invention.

Claims

1. A multi-layered oxide material based on oxygen valence change, characterized in that: With Mg and Mn as the main elements, and a small amount of other elements doped, its chemical formula is Na x Mg a Mn b M c O2, M is a combination of multiple elements among Ni, Cu, Zn, Fe, Co, Li, Al, and Ti, M type ≥ 4, 0.6≤x≤0.72, 0.15≤a≤0.33, 0.45≤b≤0.8, 0.01≤c≤0.31, a+b+c=1.

2. The multi-layered oxide material based on oxygen valence change according to claim 1, characterized in that: The layered oxide material may be: So 0.62 Mg 0.20 Cu 0.03 Zn 0.03 Ni 0.03 Feb 0.04 Mr 0.64 Tea 0.03 、 Na 0.67 Mg 0.19 Cu 0.04 Zn 0.04 Ni 0.04 Fe 0.04 Mn 0.50 Ti 0.15 or The 0.70 Mg 0.24 The 0.03 Zn 0.03 Aunt 0.03 Al 0.04 Mn 0.48 Water 0.15 O2。 3. A method for preparing a multi-layered oxide material based on oxygen valence change according to claim 1 or 2, characterized in that: The preparation method is a solid phase method, comprising: The required stoichiometric amounts of sodium carbonate or sodium nitrate, magnesium oxide, manganese dioxide and oxide or carbonate of M are mixed in proportion to form a precursor, wherein M is Ni 2+ , Cu 2+ 、Zn 2+ , Fe 3+ 、Co 3+ , Li + 、Al 3+ 、Ti 4+ of various kinds; The precursors are uniformly mixed by a grinding method to obtain precursor powder; Pre-sintering the precursor powder at 400-600° C. for 3-6 hours; Take out the pre-sintered product, grind it thoroughly, and then sinter it at 800-1100℃ for 12-24h; The heat-treated product is fully ground to obtain the layered oxide material.

4. The method for preparing a multi-layered oxide material based on oxygen valence change according to claim 3, characterized in that: The precursor is Na2CO3 or NaNO3, MgO, MnO2, and oxides or carbonates of M are mixed in a desired stoichiometric ratio according to the molar ratio of each element in the layered oxide material, wherein M is Ni 2+ , Cu 2+ 、Zn 2+ , Fe 3+ 、Co 3+ , Li + 、Al 3+ 、Ti 4+ Among them, Ni 2+ , Cu 2+ 、Zn 2+ , Fe 3+ 、Co 3+ , Li + 、Al 3+ The molar percentages of Ti and 4+ The molar percentage is selected in the range of 0.02-0.

15.

5. The method for preparing a multi-layered oxide material based on oxygen valence change according to claim 3, characterized in that: After the precursor powder is obtained, the precursor powder is pre-sintered in a muffle furnace at 500° C. for 5 hours, taken out and fully ground, and then sintered again in a muffle furnace at 900° C. for 15 hours.

6. A method for preparing a multi-layered oxide material based on oxygen valence change according to claim 1 or 2, characterized in that: The preparation method is a sol-gel method, comprising: Sodium acetate or sodium sulfate, nitrate, acetate or sulfate containing magnesium, manganese and doping element M are dissolved in water or ethanol in a stoichiometric ratio according to the molar ratio of each element in the layered oxide material to form a precursor solution; M is specifically Ni 2+ , Cu 2+ 、Zn 2+ , Fe 3+ 、Co 3+ , Li + 、Al 3+ 、Ti 4+ of various kinds; Stirring at 60°C-100°C, adding a proper amount of chelating agent, and evaporating to dryness to form a precursor gel; Pre-calcining the precursor gel in an air atmosphere at 400° C. to 600° C. for 3 to 6 hours; Then heat treat at 800℃-1100℃ for 12-24 hours; The heat-treated product is fully ground to obtain the layered oxide material.

7. The method for preparing a multi-layered oxide material based on oxygen valence change according to claim 6, characterized in that: The amount of sodium acetate or sodium sulfate used is 100 wt% to 108 wt% of the stoichiometric amount of sodium required.

8. The method for preparing a multi-layered oxide material based on oxygen valence change according to claim 6, characterized in that: The chelating agent uses citric acid in a stoichiometric amount of 100% to 200% molar ratio of all salts.

9. Use of a multi-layered oxide material based on oxygen valence variation according to claim 1 or 2, characterized in that: It is used as the positive electrode material for sodium-ion batteries.

10. The use of the multi-layered oxide material based on oxygen valence change according to claim 9, characterized in that: The multi-layered oxide material based on oxygen valence change is mixed with a conductive agent and a binder in proportion, and then evenly coated on a current collector aluminum foil, and then cut into positive electrode sheets of a sodium ion battery after drying.

11. The use of the multi-layered oxide material based on oxygen valence change according to claim 10, characterized in that: The mass ratio of the oxygen-valence-varied multi-layered oxide material powder to the conductive agent and the binder is 8:1:

1.

12. The use of the multi-layered oxide material based on oxygen valence change according to claim 10, characterized in that: The conductive agent may be carbon nanotubes, and the binder may be PVDF.